IMPLEMENTASI PEMBELAJARAN DIFERENSIASI BAGI SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI DI SEKOLAH DASAR: Indonesia - Parningotan Siagian, Yosua Marasi; Binsar Tison Gultom; Meliana Br Gultom; Bernard Simanjuntak; Rindu Erwin S.M. Marpaung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of differentiated instruction for students with special needs in an inclusive elementary school, specifically at SD Swasta YP HKBP Pematangsiantar. The research employed a qualitative approach using a case study design to obtain an in-depth understanding of how differentiated instruction is applied in real classroom settings. The research participants included the school principal, classroom teachers, special assistant teachers, and students with special needs as observation subjects. Data were collected through participatory observations, semi-structured interviews, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data reduction, data display, and conclusion drawing. The findings reveal that differentiated instruction was implemented through adaptations in content, process, product, and assessment. Teachers designed adaptive lesson plans with tiered learning objectives, simplified worksheets, scaffolding strategies, and flexible learning time for students with special needs. Collaboration between classroom teachers and special assistant teachers played a significant role in supporting effective implementation. Individualized approaches and motivational reinforcement also contributed to improving students’ participation and self-confidence. However, several challenges were identified, including limited professional training, administrative workload, and teacher–student ratio. The study concludes that differentiated instruction serves as an effective pedagogical strategy in promoting inclusive education that is responsive to student diversity.